2021
DOI: 10.3389/fcell.2021.670980
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Target of Rapamycin Complex 2 Regulation of the Primary Human Trophoblast Cell Transcriptome

Abstract: Mechanistic Target of Rapamycin Complex 2 (mTORC2) regulates placental amino acid and folate transport. However, the role of mTORC2 in modulating other placental functions is largely unexplored. We used a gene array following the silencing of rictor to identify genes regulated by mTORC2 in primary human trophoblast (PHT) cells. Four hundred and nine genes were differentially expressed; 102 genes were down-regulated and 307 up-regulated. Pathway analyses demonstrated that inhibition of mTORC2 resulted in increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 58 publications
0
7
1
Order By: Relevance
“…As expected rictor knockdown inhibited trophoblast System A uptake but raptor inhibition failed to decrease System A activity in this series. This was inconsistent with previous results [9,10] but we have no clear explanation for this difference. System L uptake was not impacted by either rictor or raptor knockdown.…”
Section: Oa-stimulated Pht Amino Acid Uptakecontrasting
confidence: 99%
See 2 more Smart Citations
“…As expected rictor knockdown inhibited trophoblast System A uptake but raptor inhibition failed to decrease System A activity in this series. This was inconsistent with previous results [9,10] but we have no clear explanation for this difference. System L uptake was not impacted by either rictor or raptor knockdown.…”
Section: Oa-stimulated Pht Amino Acid Uptakecontrasting
confidence: 99%
“…4 For example, mTORC1 activation influences the plasma membrane trafficking of the specific amino acid transporter isoforms SLC38A2 (sodium dependent neutral amino acid transporter 2, a System A transporter isoform) and SLC7A5 (LAT1, a System L transporter isoform) by regulating Nedd4-2 mediated ubiquitination 9 and mTORC2 regulates the actin skeleton responsible for insertion of amino acid transporters in the microvillous plasma membrane. 10 Previous studies in cancer cell lines have demonstrated that mTOR also acts as a lipid sensor and phosphatidic acid (PA), a key intermediate of de novo phospholipid and triglyceride biosynthesis, is the form of lipid that modulates mTOR activity. 11 During pregnancy, maternal fatty acids modulate an array of placental functions including development of extravillous trophoblast cells, lipid droplet formation, and amino acid uptake.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established method involving sequential trypsin digestion and Percoll centrifugation [ 30 , 79 ] was used to isolate and culture primary human trophoblast (PHT) cells. Briefly, isolated PHT cells were plated at 1.5 × 10 6 per well in six-well plates and cultured in a 1:1 mixture of Dulbecco’s modified Eagle’s medium (DMEM, 25 mM glucose) and Ham’s F12 medium (10 mM glucose) with 2 mM glutamine, 50 μg/mL gentamicin, 60 μg/mL penicillin, 100 μg/mL streptomycin, and 10% fetal bovine serum.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, mTOR regulates glucose uptake in trophoblast-derived cell line cultures 33 . Both mTORC1 and mTORC2 signaling regulate trophoblast expression of various genes involved in ribosome biosynthesis, inflammation, micronutrient transport, and angiogenesis, representing novel links between mTOR signaling and multiple placental functions necessary for fetal growth and development 34,35 . However, data unequivocally demonstrating that changes in trophoblast mTOR signaling regulate placental function in vivo are lacking.…”
Section: Introductionmentioning
confidence: 99%